(3GdGOGQI GdGSJQGJjLjI (B/s - (3SGde, eMeO Ydjs ((3YeGf(B: s (3OGQ GdHOGjI(B, s, 2009)
(3eGgjI GdGOGQI GdGSJQGJjLjI , JMdjd GdHjFI GdGSJQGJjLjI ,JMdjd GdehGQO , JMdjd Gdbje h GdSdWI , JMdjd GdGgOGa h GdJhbYGJ , JWhjQ GdHOGFd GdGSJQGJjLjI , GdJbjjeGdGSJQGJjLj h GdGNJjGQ , JNWjW GdehGQO , Gdgjcd GdJfXjej , GdCaQGO h GdfXe(B.s
(3eQGLY U(B.197s
Keywords: (3GdGOGQIs; (3GdEOGQI GdYGeIs; (3GdEOGQI GdeQcRjIs; (3GdJNWjW hGdJbjjes